Towards a trans-disciplinary concept of failure for Integrated Product Development. (1st January 2011) - Del Frate, L.; Franssen, M.; Vermaas, P.E.
Integrated product design approaches presuppose knowledge sharing among cross-functional teams. In this paper, such sharing is considered for failure phenomena. It aims at finding a trans-disciplinary definition of failure that facilitates the communication of knowledge about failures between the different engineering disciplines. Four criteria are given that a trans-disciplinary definition of failure should meet, and a survey of engineering proposals to define failure is presented. It is shown that none of these existing definitions meets all four criteria, and that six come close by meeting three criteria. Finally, analysing these six definitions, a trans-disciplinary definition of failure is proposed.